Fixing the “Oops” Moment: Glueing Up Pulmonary Artery Pseudoaneurysm after a Lung Biopsy - Sreedhara B. Chaluvashetty; Roshan Valentine; Krishnendhu M. S.; Trupthi Das; Reddi Prasad Yadavali (Indian Journal of Radiology and Imaging)
Computed tomography-guided lung biopsy is a common procedure performed to obtain adequate tissue not just for diagnosis but also for molecular typing. Hemothorax is a rare yet serious complication of percutaneous lung biopsies with reported incidence of 0.092%. This is most commonly due to the injury to the intercostal artery or internal mammary artery. However, bleeding due to pulmonary artery involvement is rare and we report one such case which was managed by percutaneous glue embolization.